Planned topics Department of Religious Studies 1991-2013 - Journal, Editorial board of the (Ukrai͏̈ns'ke relihijeznavstvo, 2013)
Department of Religious Studies of the Institute of Philosophy of the National Academy of Sciences of Ukraine and its departments and n / d groups in 1991-2013.